The Walking Catfish - Day, David, 1947-; Entwisle, Mark, 1961-; Day, David, 1947- (New York : Macmillan, 1991)
A tall tale about a Big Lie Contest at which a tale about a giant catfish becomes true and swallows its teller.
"First published in 1991 by Picadilly Press, London, England as The big lie"--P. opp. t.p.
Keywords: Tall tales